Anti-Müllerian hormone: biology and role in endocrinology and cancers - Gowkielewicz, Marek; Lipka, Aleksandra; Zdanowski, Wojciech; Waśniewski, Tomasz; Majewska, Marta; Carlberg, Carsten (Frontiers in Endocrinology, 2024)
Anti-Müllerian hormone (AMH) is a peptide belonging to the transforming growth factor beta superfamily and acts exclusively through its receptor type 2 (AMHR2). From the 8 th week of pregnancy, AMH is produced by Sertoli cells, and from the 23 rd week of gestation, it is produced by granulosa cells of the ovary. AMH plays a critical role in regulating gonadotropin secretion, ovarian tissue responsiveness to pituitary hormones, and the pathogenesis of polycystic ovarian syndrome. It inhibits the transition from primordial to primary follicles and is considered the best marker of ovarian reserve. Therefore, measuring AMH concentration of the hormone is valuable in managing assisted reproductive technologies. AMH was initially discovered through its role in the degeneration of Müllerian ducts in male fetuses. However, due to its ability to inhibit the cell cycle and induce apoptosis, it has also garnered interest in oncology. For example, antibodies targeting AMHR2 are being investigated for their potential in diagnosing and treating various cancers. Additionally, AMH is present in motor neurons and functions as a protective and growth factor. Consequently, it is involved in learning and memory processes and may support the treatment of Alzheimer's disease. This review aims to provide a comprehensive overview of the biology of AMH and its role in both endocrinology and oncology.